2017
DOI: 10.1017/aog.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Changing contribution of peak velocity events to annual velocities following a multi-decadal slowdown at White Glacier

Abstract: As the focus of intensive glaciological studies in the 1960–70s, White Glacier on Axel Heiberg Island, Canada, has played an important role in understanding the dynamics of mostly-cold polythermal glaciers in the high Arctic. In this study, we examine the magnitude, duration and timing of peak velocity events in the summers of 2013–15 using continuous dual-frequency GPS observations, and compare them with similar measurements made in 1968. Summer speed-up events in 1968 and 2014, in which ice velocities reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Similarly, Stevens et al (2016) observed at North Lake net annual flow deceleration of 1.1% per year during 2009-2013. Analogous multi-year slow-down trends of glaciers have been observed in Alaska (Truffer et al, 2005;Burgess et al, 2013) and Canada (Thomson and Copland, 2017).…”
Section: Decadal Ice Flow Variabilitysupporting
confidence: 57%
“…Similarly, Stevens et al (2016) observed at North Lake net annual flow deceleration of 1.1% per year during 2009-2013. Analogous multi-year slow-down trends of glaciers have been observed in Alaska (Truffer et al, 2005;Burgess et al, 2013) and Canada (Thomson and Copland, 2017).…”
Section: Decadal Ice Flow Variabilitysupporting
confidence: 57%
“…The possible reason for slight seasonal variation at points A2, B2 and F is that the glacier is poly-thermal with cold ice around its margins where ice is thin. In the studies of [1,22,26,41], daily or weekly velocity variations during summer can be clearly seen from observations. In our study, GPS observations at AL are only available in late April and early September, which means only the mean velocities between April and September can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…To ascertain how glaciers behave in the present and future, it is necessary to further investigate the ice flow velocity of glaciers, because the long-term evolution of glacier velocities, which control the delivery of ice to warm, low elevation regions, is an important component of the future stability of ice masses in a warming climate [22]. Poly-thermal glaciers are glaciers that have a mixed basal thermal regime, with a warm-based core, and cold-based ice around its snout and margins [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-running observational records of glacier dynamics pre-dating c1984 (the launch of Landsat-5, e.g., Dehecq and others, 2019) are sparse globally. Several of these sites have remained the focus of continuous observation across several decades (Fischer and others, 2015; O'Neel and others, 2019) while others have only recently been re-established (Thomson and Copland, 2017a; Armstrong and others, 2020). These provide a growing geographic distribution of long-running datasets that may help identify multi-decadal dynamics missed in common parameterizations of glacier flow.…”
Section: Introductionmentioning
confidence: 99%